Pengaruh Earnings Management Terhadap Financial Performance Dengan Earnings Quality Sebagai Variabel Intervening - Steven Sanjaya; Devie Deviesa (Business Accounting Review, 2017)
Financial report is a accountability of management of the company, which is indirectly represent the good and the bad performance of a company. For external side, the financial statements are the primary tools of communication media with internal side. Nowadays, there are many methods that can be done by management in managing the company’s financial statements. Earnings management is one of the action that could affect the company’s financial performance that is useful for investors. This study aimed to know the extent of the affect of earnings management to financial performance.The sample of this study was LQ45 companies that listed in Indonesian Stock Exchange in period 2012-2015. The data processing method done by using validity, reliability, and statistic descriptive analysis. While the data analysis method is used SPSS and Partial Least Square (PLS) to know the relationship between variables. The result revealed that, earnings management significantly affect financial performance directly, and indirectly through the intervening variables which was earnings quality.